PARENTS’ SYMBOLIC BEHAVIOR IN EDUCATING CHILDREN: A GENDER PERSPECTIVE - Syaiful Marwan; Aulia Muswara (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
This study is aimed at describing parents’ symbolic behavior in educating children. This behavior is displayed symbolically in the form of parenting. Parenting is carried out are in a perspective of gender: boys and girls. Data were collected through literature review from various sources based on experts’ judgements and in accordance with public opinion of educating children in a family. The result shows that in educating children, both parents are obliged to provide positive symbolic behavior because it will have an impact on children behavior as reactions and consumption in satisfying impulses in the form of responses of parents’ symbolic behavior in educating children.